Spectroscopic ellipsometry investigation on the excimer laser annealed indium thin oxide sol-gel films - Noh, Miru; Seo, Ilwan; Park, Junghyun; Chung, J. -S.; Lee, Y. S.; Kim, Hyuk Jin; Chang, Young Jun; Park, J. -H.; Kang, Min Gyu; Kang, Chong Yun (ELSEVIER SCIENCE BV, 2016)
We report on the effect of the excimer laser annealing on the electronic properties of indium tin oxide (ITO) sol-gel films by using spectroscopic ellipsometric technique. We found that the excimer laser annealing effectively induces the crystallization as well as condensation of the sol-gel film. As the laser power increased, the carrier concentration and the relaxation time of photo-annealed films increased, with the bandgap shifting to higher energies. Simultaneously, the extinction coefficient values in the visible region were reduced significantly. We suggest that the excimer laser annealing should be a promising method for low temperature preparation of the ITO film on heat-sensitive substrates via the sol-gel process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: TIN-OXIDE; ELECTRICAL-PROPERTIES; TRANSPARENT; CRYSTALLIZATION; TECHNOLOGY